The impact of local shocks on well-being: Only a matter of perception? - Wiebke Stein; Reinhard A. Weisser (Leibniz Universität Hannover, Wirtschaftswissenschaftliche Fakultät, 2018)
This paper investigates how witnessing adverse events affects individuals' perceptions and consequently their personal subjective well-being. In order to do so, we compare material well-being dynamics with changes in subjective well-being. We link GIS data on local flood shocks to an extensive household sample from rural Southeast Asia. This allows us to contrast individuals who actually experienced a shock with those who did not. We find that the mere proximity to a potentially adverse flood shock, without any direct impact on a household's material well-being, can be sufficient to affect subjective well-being.
Keywords: I31; Q51; R23; 330; perception; subjective well-being; GIS data; MODIS flood mapping